2002
DOI: 10.1046/j.1468-1331.2002.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guideline on mild traumatic brain injury: report of an EFNS task force

Abstract: In 1999, a Task Force on Mild Traumatic Brain Injury (MTBI) was set up under the auspices of the European Federation of Neurological Societies. Its aim was to propose an acceptable uniform nomenclature for MTBI and definition of MTBI, and to develop a set of rules to guide initial management with respect to ancillary investigations, hospital admission, observation and follow‐up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
221
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(239 citation statements)
references
References 118 publications
5
221
1
7
Order By: Relevance
“…According to our hospital protocol, a neurologist and/or neurosurgeon is consulted at the ED in case a head trauma patient presents with i) a Glasgow Coma Scale (GCS) of 3-14, or ii) a GCS of 15 with loss of consciousness (LOC) and/or posttraumatic amnesia (PTA), or iii) a GCS of 15 without LOC and PTA, but fulfilling additional criteria: unclear or ambiguous accident history, persisting or progressive headache, nausea and vomiting, intoxication with alcohol or drugs, epileptic seizures, coagulation disorders, platelet aggregation inhibitors or oral anticoagulation use, confusion, disorientation, feeling dazed, retrograde amnesia, focal neurological deficits, age O60 or !2 years, high-energy accident, or visible trauma above the clavicles (including signs of skull (base) fracture) (23). According to the hospital admission GCS, TBI patients are classified as mild (GCS 13-15), moderate (Mod) (GCS 9-12), or severe (GCS %8) (23,24). In RUBICS, we register various clinical variables obtained from the ambulance or helicopter trauma physician, the ED, the intensive care unit (ICU), and the neurological and neurosurgical ward.…”
Section: Methodsmentioning
confidence: 99%
“…According to our hospital protocol, a neurologist and/or neurosurgeon is consulted at the ED in case a head trauma patient presents with i) a Glasgow Coma Scale (GCS) of 3-14, or ii) a GCS of 15 with loss of consciousness (LOC) and/or posttraumatic amnesia (PTA), or iii) a GCS of 15 without LOC and PTA, but fulfilling additional criteria: unclear or ambiguous accident history, persisting or progressive headache, nausea and vomiting, intoxication with alcohol or drugs, epileptic seizures, coagulation disorders, platelet aggregation inhibitors or oral anticoagulation use, confusion, disorientation, feeling dazed, retrograde amnesia, focal neurological deficits, age O60 or !2 years, high-energy accident, or visible trauma above the clavicles (including signs of skull (base) fracture) (23). According to the hospital admission GCS, TBI patients are classified as mild (GCS 13-15), moderate (Mod) (GCS 9-12), or severe (GCS %8) (23,24). In RUBICS, we register various clinical variables obtained from the ambulance or helicopter trauma physician, the ED, the intensive care unit (ICU), and the neurological and neurosurgical ward.…”
Section: Methodsmentioning
confidence: 99%
“…5,10,29,32,34) Mechanisms of injury as indications for CT include pedestrian struck by motor vehicle or occupant ejected from motor vehicle, falling from height À3 feet or five stairs, 29) involvement in a high-energy accident, and unclear or ambiguous mechanisms. 34) Our study also revealed that patients falling from stairs or height and pedestrians in motor vehicle accidents were likely to have intracranial injury. Patients sustaining fall, assault, or crush injury are at risk of intracranial injury compared with patients involved in motor vehicle crashes.…”
Section: Ct Indications In Mild Head Injurymentioning
confidence: 99%
“…Therefore, CT should be the first choice in patients with suspected intracranial lesion. 28) The indication for skull radiography is limited to patients with GCS score 15 and only LOC/amnesia, 34) one other symptom, 5,24,32,34) or symptoms without vomiting, but only if CT is recommended but not available. 25) Many studies have reported increased risk of intracranial lesions in patients with head injury aged over 65 years 9,29) or over 60 years.…”
Section: Ct Indications In Mild Head Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in current guidelines discussing head injury and warfarin use, liberal CT scanning of the head seems to be a reasonable strategy, even for those who present with normal mental status and a GCS score of 15. [10][11][12][13] The risk of delayed bleeding appears to be very close to zero with clopidogrel, suggesting that routine hospitalization and follow-up scanning might not be necessary. Patients taking warfarin are not without risk and probably do require follow-up but not necessarily routine (second) CT.…”
Section: Resultsmentioning
confidence: 99%